New tele-diagnostic model using volume sweep imaging for rural areas - Ferrer J. (2017)
Advances in information and communications technologies provide a new opportunity to improve the access to healthcare in remote rural areas (RA) where there is a lack of infrastructure and medical experts. This paper implements a new model for tele-ultrasound (US) based on volumetric sweep imaging protocols specially designed for the acquisition of US. Non-physician health personnel from the RA are trained on the use of these protocols in a few days. The operator utilizes the medical box (MB), a specially designed telecommunication system, to guide, compress, encrypt and transmit the US sweeps through the cloud to the radiologist who performs the diagnosis remotely. The report is automatically sent back to the MB. The system was able to send US volumetric images with poor connectivity conditions in 6 minutes on average. These results of implementing this tele-ultrasound model in RAs are encouraging and support future validations.